Cave use and palaeoecology at Maludong (Red Deer Cave), Yunnan, China. (August 2016) - Ji, Xueping; Curnoe, Darren; Taçon, Paul S.C.; Zhende, Bao; Ren, Liang; Mendoza, Raynold; Tong, Haowen; Ge, Junyi; Deng, Chenglong; Adler, Lewis; Baker, Andy; Du, Bin
Abstract: Maludong is a Terminal Pleistocene fossil-bearing cave located on the northern edge of the Southeast Asian tropical zone, southeastern Yunnan Province. Hominins from the cave include remains with affinities to archaic hominins and others with an apparent mixture of archaic and modern traits all deriving from deposits dating from the Bølling-Allerød interstadial. The sedimentary sequence of the cave appears to be largely anthropogenic in origin and records a nearly continuous record of fire lasting close to 1000 years. The fauna comprise only extant taxa and point to a rather biased sample with a preponderance of artiodactyls and carnivores, many of which show evidence for anthropogenic breakage and burning. A new analysis of the mammal fauna recovered during excavation, palaeohabitat reconstruction and stable isotope analysis of deer teeth and bones indicates the cave was located within or close to a closed forest environment. The mammal taxa also indicate a large body of water existed in the vicinity of Maludong, suggesting the modern lakes Datun Hai and Chang Qiao Hai were much larger at the time. Maludong may document an entirely novel ecological and behavioural scenario involving archaic and modern human interaction, economic exploitation and ceremonial behavior involving secondary burial practices.